PERDAS DE AMÔNIA POR VOLATILIZAÇÃO DE FONTES E DOSES DE NITROGÊNIO NA CULTURA DO MILHO - ZACARIAS JUNIOR, Cleyton Fernando Martins; ROCHETTI, Ramon Cellin; SILVEIRA, José Eduardo Correa; PUPIM, Rafael de Souza; FAGUNDES, Mauricio Pereira; ALVES, Ana Carolina (ANAIS DO ENIC, 2020)
-